Albumin Coating Prevents Cardiac Effect of the Magnetic Nanoparticles - Nunes, Allancer D. C.; Gomes-Silva, Lorrany A.; Zufelato, Nicholas; Prospero, Andre G. [UNESP]; Quini, Caio C. [UNESP]; Matos, Ronaldo V. R. [UNESP]; Miranda, Jose R. A. [UNESP]; Bakuzis, Andris F.; Castro, Carlos H. (Institute of Electrical and Electronics Engineers (IEEE), 2019)
We have showed that surface layer can determine cardiac effects of the magnetic nanoparticles (MNPs). Considering the high binding capacity of albumin and low side-effects, the aim of this study was to evaluate the influence of albumin coating on the cardiovascular effects of two manganese ferrite-based MNPs: citrate-coated and bare MNPs. Isolated rat hearts were perfused with citrate-coated magnetic nanoparticles (CiMNPs), citrate albumin-coated magnetic nanoparticles (CiAlbMNPs), bare magnetic nanoparticles (BaMNPs), and albumin-coated magnetic nanoparticles (AlbMNPs). CiMNPs induce a transient decrease in the left ventricular end-systolic pressure, +dP/dt and -dP/dt. These effects were not worsened by albumin coating. BaMNPs significantly increased the left ventricular end-diastolic pressure and perfusion pressure and decreased the +dP/dt and -dP/dt. These effects were completely absent in hearts perfused with AlbMNPs. None of the MNPs changed heart rate or arterial blood pressure in conscious rats. Magnetic signals in isolated hearts perfused with BaMNPs were significantly higher than AlbMNPs perfused hearts. However, the magnetic signal in heart tissue was similar when the MNPs were infused in conscious rats. These data indicate that albumin-coated can reduce cardiovascular effects of MNPs. These findings suggest a protective effect of albumin surface in MNPs, favoring its future therapeutic applications.
Keywords: albumin-coated; cardiac function; magnetic fluids; Magnetic nanoparticles; nanomedicina